Pengaruh Good Corporate Governance dan Corporate Social Responbility terhadap Kinerja Keuangan pada Perbankan yang Terdaftar di BEI Periode 2017-2020 - Salma Andhika Puteri; Gendro Wiyono; Risal Rinofah (Ekonomis: Journal of Economics and Business, 2023)
The implementation of Good Corporate Governance and Corporate Social Responsibility is important for a company. By implementing Good Corporate and Corporate Social Responsibility properly and correctly it will add to the image of the company, this will also improve the company's financial performance. This study aims to determine the effect of independent commissioner, board of directors, audit committee and Corporate Social Responsibility variables on financial performance in banks listed on the IDX. The sampling technique in this study used purposive sampling which produced 29 samples over 4 years, namely 116 samples. The analytical method used was multiple regression analysis which was processed using SPSS version 25. The results showed that only the board of directors had an effect on financial performance, while independent commissioners, audit committees and CSR had no effect on financial performance. Together with independent commissioners, boards of directors, audit committees, and corporate social responsibility affect financial performance.